The annealing effect on microstructure and ESR properties of (Cu/Ni) co-doped ZnO nanoparticles - GÜLER, ADİL; BOYRAZ, CİHAT (ELSEVIER SCI LTD, 2019)
Zn0.94Cu0.01Ni0.O-05 nanoparticles were synthesized by sol-gel technique and annealed under varying wide temperature range (450, 500, 550, 600, 700, 800, and 900 degrees C). Differential thermal analysis (DTA), and thermo gravimetric analysis were performed using a wide temperature range with optimizing the annealing temperature and clarifying the possible weight losses. The structural variation of nanoparticles with dopant ratio and annealing temperature were studied by X-ray diffraction technique and we found that the nanoparticles annealed at 450, 500 and 550 degrees C were optimum annealing temperatures with the property of single phase with ZnO wurtzite hexagonal structure. Above 550 degrees C, two phases were observed, namely ZnO and NiO. A slight temperature dependent less structural distortion was revealed with NiO phase especially after the sample annealed at 550 degrees C. The microstructural parameters were also presented. Cluster shape random agglomeration was observed in all frames of SEM images obtained by different annealing temperatures. Detailed Electron Spin Resonance (ESR) measurements were performed to reveal the magnetic behaviour of all nanoparticles.
Keywords: Cu/Ni doped ZnO; Magnetic properties; Sol-gel method; Nanostructures; THIN-FILMS; NI; FERROMAGNETISM; SEMICONDUCTOR; OXIDE